Synthetic Analogues of Betulinic Acid as Potent Inhibitors of PS1/BACE1 Interaction to Reduce Aβ Generation. Issue 1 (20th December 2016) - Zhang, Chenlu; Wang, Xiaoyin; Cui, Jin; Li, Xiaohang; Zhang, Yangming; Wang, Xin; Gu, Haifeng; Li, Wei; Xie, Xin; Zhao, Jian; Pei, Gang; Nan, Fajun
Abstract: The lupane‐type triterpenoids are endowed with a wide range of biological activities such as antiviral, anti‐inflammatory and anticancer activity. We describe here its potential application in Alzheimer's disease (AD) treatment as an inhibitor of PS1/BACE1 interaction. 3‐ α ‐Akebonoic acid, which emanated from a high throughput screening (HTS), was discovered to interfere with PS1/BACE1 interaction and reduce amyloid β‐protein (Aβ) production. In view of the limited source, we instead used naturally rich betulinic acid (compound2 ) as starting material for lead optimization and a focused library of its derivatives was constructed to gain a better understanding of the structure activity relationship (SAR) of triterpenoid‐type inhibitor of PS1/BACE1 interaction. Compound22 was finally chosen as the most potent PS1/BACE1 interaction inhibitor, which reduced Aβ generation effectively. Abstract :